2016
DOI: 10.5935/0103-5053.20160182
|View full text |Cite
|
Sign up to set email alerts
|

PhotoMetrix: An Application for Univariate Calibration and Principal Components Analysis Using Colorimetry on Mobile Devices

Abstract: This article describes the development of a mobile colorimetric analysis tool. The application, called PhotoMetrix, employs the techniques of simple linear correlation for univariate analysis and principal components analysis (PCA) for multivariate exploratory analysis. The image data are captured by the main camera of the device and converted into red, green and blue (RGB) histograms. As regards the application, the iron determinations were performed in vitamin supplements (univariate module) and differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 9 publications
(9 reference statements)
1
39
0
16
Order By: Relevance
“…From the five samples that had been analyzed, the sample of fried tempe shows 5% and 10% of wax concentration which is indicated on quadrants of K2 and K3 (Figure 3). The test result is in accordance with the research conducted by Helfer and other researchers who provide the ability of Photometrix ® application in grouping banknotes based on their color from different countries based on the paper used (Helfer et al 2017). As a comparative method, TLC test was conducted and it showed that there were spots on the sample of fried tempe with Rf value of 0.52 and 0.50 which is equivalent to Rf value of the sample of cooking oil which is deliberately added wax.…”
Section: Application Methods On Gorengan Samplesupporting
confidence: 87%
See 1 more Smart Citation
“…From the five samples that had been analyzed, the sample of fried tempe shows 5% and 10% of wax concentration which is indicated on quadrants of K2 and K3 (Figure 3). The test result is in accordance with the research conducted by Helfer and other researchers who provide the ability of Photometrix ® application in grouping banknotes based on their color from different countries based on the paper used (Helfer et al 2017). As a comparative method, TLC test was conducted and it showed that there were spots on the sample of fried tempe with Rf value of 0.52 and 0.50 which is equivalent to Rf value of the sample of cooking oil which is deliberately added wax.…”
Section: Application Methods On Gorengan Samplesupporting
confidence: 87%
“…G channel on Photometrix ® application is selected as measurement channel because it has r value approaching ± 1. This shows relationship between wax concentrations in cooking oil with color intensity that is produced (Helfer et al, 2017). The result of linearity measurement of wax analysis in cooking oil was conducted to seven different wax solutions with 1% until 25% concentration detected by smartphone presented in Figure 1.…”
Section: Results and Discussion The Results Of Selection And Optimizatmentioning
confidence: 94%
“…O uso de imagens digitais vem sendo aplicado em análises que eram restritas a equipamentos como colorímetros, espectrofotômetros e fluorômetros. 11 A análise de imagens digitais associada à análise multivariada permite o desenvolvimento de procedimentos simples, rápidos, não destrutivos e de baixo custo. O uso dessas imagens obtidas por scanners, câmeras digitais e outros, fornece resultados tão precisos quanto os instrumentos associados com análise multivariada.…”
Section: Artigounclassified
“…Diversos estudos, utilizando o aplicativo PhotoMetrix como ferramenta de análises, vem sendo realizado como a caracterização de tanino por PCA demonstrando o desenvolvimento de um método rápido, não destrutivo e de baixo custo. 12 Entre as aplicações reportadas estão: (i) quantificação de etanol em cachaça, 16 (ii) quantificação de ferro em suplementos vitamínicos e aplicabilidade em cédulas de Real, podendo diferenciá-las de cédulas de Peso argentino de maneira eficaz por PCA, 11 (iii) análise indireta de iodo no biodiesel, 17 (iv) estabilidade térmica do leite, 18 (v) identificação de taninos em amostras comerciais 12 e (vi) monitoramento de flúor em água. 19 Assim, visto a crescente incidência de casos de adulteração e fraudes em documentos, e a necessidade de métodos que exijam pouca manutenção, fácil operação, mínimo preparo de amostra, baixo custo, entre outros fatores, este trabalho objetiva avaliar uma nova metodologia para análise de autenticidade de cédulas de reais de R$10, 20, 50 e 100, buscando alcançar essas necessidades por meios de métodos quimiométricos aliados à análise de imagem digital.…”
Section: Artigounclassified
“…In this context, we used a free software app called PhotoMetrix [15] to estimate the enzymatic activity of endoglucanase enzymes. PhotoMetrix has been used for efficiently helping to determine iron in vitamin supplement tablets [16], iodine in biodiesel [17], ethanol in sugarcane spirit samples [18], and for monitoring of acid-base titrations on paper platforms [19], estimation of pH in milk samples [20] and chromium speciation in leather samples [21].…”
Section: Introductionmentioning
confidence: 99%